This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: I. Problem 1 1. Part 1 a) S pvt = (X – T) – C b) S pvt = (Y – T) – m(Y – T) c) S pvt = (1 – m)(Y – T) 2. Part 2 a) S gov = T – G b) S d = S pvt + S gov c) S d = (1 – m)(Y – T) + (T – G) d) S d = (1 – m)Y + mT – G 3. Part 3 a) Part 3a 1. A myopic consumer is by definition unconcerned with the future, so the interest rate (which determines the relative value of present savings in the future ) is immaterial. b) Part 3b 1. When taxes increase by an amount Δ T, S pvt decreases by an amount (1 – m)T; where 0 ≤ 1 – m ≤ 1. 2. When taxes increase by an amount Δ T, S gov increases by an amount Δ T. 3. Δ S d = Δ S pvt + Δ S gov = – (1 – m)T + T = mT. Since m and T are both positive, Δ S d is positive and S d experiences an increase. This is because government saving increases exactly with T and private saving decreases fractionally with T, so an increase T increases total saving. c) Part 3c 1. A utility-maximizing consumer knows that an increase in present government spending (with taxes held constant) implies an increase in future government taxation. Therefore, he will increase savings in order to smooth consumption over the two periods. Since these two effects work in opposite directions, the effect of the decrease in government spending is mitigated and saving decreases by an amount less than Δ G. However, with a myopic consumer, the consumer does not foresee the future taxation increase and does not change saving in response to an increase in present government spending. Therefore, the decrease in saving is equal to the decrease in government saving which is equal to Δ G. Therefore, the decrease is saving resulting from an increase in present government spending is larger with a myopic consumer than with a utility-maximizing consumer. 4. Part 4 a) S d (r (+) | Y (+), T (+), G (–)) b) I d (r (–) | A f (+), K (–)) c) IS (r (–) | T (–), G (+), A f (+), K (–)) 5. Part 5 a) S d = (1 – m)Y + mT – G b) Δ S d = (1 – m) Δ Y + m Δ T – Δ G c) Δ S d = 0, Δ T = 0 d) 0 = (1 –m) Δ Y – Δ G e) Δ Y = Δ G/(1 –m) 6. Part 6 a) An increase of Δ G in government spending will not shift the S d curve if coupled with a simultaneous increase of Δ G/(1 –m) in Y....
View Full Document
- Fall '07
- Macroeconomics, Liquidity preference, IS/LM model, Relative Values, Af Nf